Factors that influence happiness of nursing students according to COVID-19 infection status - Hyun-Ok Jung; Seung-Woo Han (BMC, 2024)
Abstract Background Happiness is a cognitive and emotional evaluation of one's life, and the upward approach affects satisfaction and happiness throughout life. Because nursing students must experience medical settings closely related to COVID-19 infection through clinical practice, they are vulnerable to exposure to infection and academic stress, and are also sensitive to personal life satisfaction and happiness. In this study, Korean nursing students who experienced the COVID-19 pandemic during the COVID-19 endemic era were divided into nursing students infected with COVID-19 and non-infected nursing students. By identifying the effects of college life adaptation, leisure satisfaction from club activities, and family health on happiness, which are individual sub-factors of happiness, we intend to provide basic data for the development of intervention programs for promoting their happiness. Methods Data were collected from October 4, 2023 to November 15, 2023. The subjects were 343 students enrolled in five nursing schools in four major cities (D, G, K, and Y) in Korea. Data were analyzed using descriptive statistics, t-test, one-way ANOVA, Pearson's correlation coefficients. Results For COVID+ students, happiness was significantly affected by adaptation to campus life and family strengths. This model had r2 = 0.401; i.e., it explained 40.1% of the variability in happiness. For COVID0 students, happiness was significantly affected by adaptation to campus life and subjective health status, with r2 = 0.346. Conclusions These results indicate the necessity of developing a happiness-promotion program for nursing students.